The Medici Chapel: A Semantic Aspect - Kostyria, Maksim A. (Actual Problems of Theory and History of Art, 2016)
The Medici Chapel (or the New Sacristy) of the Church of San Lorenzo in Florence (1520–1534) is one of the greatest masterpieces of Michelangelo Buonarroti (1475–1564) and the whole Renaissance. At the same time, it is one of the most enigmatic and polysemantic works of that epoch. The abundance of the concepts of “decoding” the New Sacristy’s imagery proposed by the previous researchers does not exhaust the depth of its content and leaves us space for new interpretations.The article focuses on the analysis of the semantic structure of the Medici Chapel. During the reconstruction of Michelangelo’s intent, the author has examined the architectural, sculptural, and pictorial elements, both implemented or not, from which the ensemble of the Medici Chapel had been drawn. Michelangelo’s masterpiece is usually considered in connection with the views of Plato, Dante, and Savonarola. The author proposes a new look at the range of ideas. The concept of the chapel, according to the author, is mainly determined by the idea of the Last Judgment. In the new interpretation of the ensemble, a crucial role is played by the sculptures of four Times of Day. The master reinterpreted the cyclical nature of these images linking them to Apocalypse of John the Evangelist (Revelation, 10: 6). It has been concluded that the concept of the imagery of the Medici Chapel embodied three conceptual complexes: Platonic dualism, Dante’s three-part structure of the underworld, and the idea of posthumous retribution in its most complete form — the Last Judgment.
Keywords: Michelangelo; the Medici Chapel; the times of day; Italy; 16th century; sculpture; Neoplatonism; Dante; “Apocalypse”; Last Judgment